2015
DOI: 10.2131/jts.40.625
|View full text |Cite
|
Sign up to set email alerts
|

Calcium ions rescue human lung epithelial cells from the toxicity of zinc oxide nanoparticles

Abstract: -Contradictory results have been reported for in vitro evaluations of whether zinc oxide nanoparticles (ZnO NPs) are cytotoxic. Though there have been reports of ZnO NPs cytotoxicity due to Zn ions released from the nanoparticles, there have also been reports concluding that Zn ions are not cytotoxic. This inconsistency is mostly attributed to the types of cells used. In this research, we investigated the difference in the level of ZnO NPs cytotoxicity due to culturing conditions. The sensitivity of human lung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…The maximum concentration of Zn +2 ion released by present multi‐ion doped HA samples was ~2.4 ppm and at this concentration no cytotoxicity on NIH3T3 cells can be seen from Figure . This understandable as the Zn +2 ion concentration up to 8 ppm do not induced any cell death and presence of Ca +2 in the culture media can upregulate the cell cycle function leading to significant decrease in the inhibitory effect of Zn +2 if any . Zinc ions also found to protect the mouse fibroblast cells from toxicity of other ions such as Co +2 .…”
Section: Resultsmentioning
confidence: 81%
“…The maximum concentration of Zn +2 ion released by present multi‐ion doped HA samples was ~2.4 ppm and at this concentration no cytotoxicity on NIH3T3 cells can be seen from Figure . This understandable as the Zn +2 ion concentration up to 8 ppm do not induced any cell death and presence of Ca +2 in the culture media can upregulate the cell cycle function leading to significant decrease in the inhibitory effect of Zn +2 if any . Zinc ions also found to protect the mouse fibroblast cells from toxicity of other ions such as Co +2 .…”
Section: Resultsmentioning
confidence: 81%
“…Most of the antibacterial compounds are of bulk complex materials having high toxicological side effects [1][2][3][4][5]. Recent studies on antibacterial activity using nanoparticles (NPs) have shown to reduce the side effects, although the data are both limited and controversial [6][7][8][9]. The antibacterial activity of NPs is attributed to their nano scale dimensions, changed electronic/optical transitions and high surface to volume ratio which leads to improved surface chemistry and quantum confinement effects [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…As well, when injected ZnO NPs intraperitoneally (20–30 nm, 25 mg/kg), there are no significant effects in Zn, Na+, and K+ level in the brain, whereas Fe and Ca2+ level were clearly reduced (Amara et al, ). Additionally, in a previous study using human lung epithelial cells, ZnO NPs‐induced cytotoicity was mitigated by supplementing the culture medium with Ca2+ (Hanagata and Morita, ). On the other hand, in other studies, ZnO NPs have been shown to disrupt intracellular calcium homeostasis by elevating intracellular Ca2+ level (Wang et al, ; Guo et al, ).…”
Section: Discussionmentioning
confidence: 99%